Community Assistance through Environmental Maintenance to Overcome Dengue Disease in Waterlog-prone Environments Season - Angelita Oktavia Permadi; Wardoyo, Arik Aguk; Putri, Inge Williandani Setya; Balkis, Nadia Noviandra; Puspitasari, Bella Lia (International Assulta of Research and Engagement (IARE), 2024)
This service aims to increase public understanding and awareness of environmental conservation to overcome the spread of dengue hemorrhagic fever (DHF) in an environment that is prone to waterlogging in the rainy season. In addition, it is also aimed at increasing understanding of environmental factors that contribute to the increase in the population of Aedes aegypti mosquitoes, overcoming challenges in increasing public awareness of the environment and developing effective strategies to encourage the adoption of pro-environmental behaviors to prevent the spread of dengue fever. This service method uses PAR (Participatory Action Research) and descriptive methods through a qualitative approach. The results of the service show that the socialization of the implementation of socialization at Kosmik Kos Putra 39 in Jember makes this educational and interactive activity increase public understanding and concern about the importance of maintaining environmental cleanliness to prevent dengue. This activity is expected to provide benefits in the form of increasing understanding, awareness, and skills of the community in protecting the environment so that it does not become a breeding ground for mosquitoes, as well as contributing to efforts to protect and manage the environment sustainably.